The Effect of Person Organization Fit and Competence on Employee Performance with Work-Life Balance as an Intervening Variable in Logistics Companies in Jakarta - Jessciha, R.A Jelitha; Noerman, Teuku (Formosa Journal of Science and Technology, 2024)
This study aims to test the research model which is expected to obtain results from the influence of Person Organization Fit and Competency on Work-Life Balance and its impact on Employee Performance. Respondent data will use the results of the distribution of questionnaires to employees of Logistics Companies in Jakarta online through the Google Drive platform to 81 employees. In this study, 5 tests were carried out on the hypothesis based on variable indicators prepared using SEM PLS (Partial Least Square) analysis using the smartPLS method. This test consists of an outer model, an inner model, and a Hypothesis test. The results of the study show that person organization fit and competence have a positive and significant effect on work-life balance. Work-life balance also has a positive and significant effect on employee performance. However, person organization fit has a positive but not significant effect on employee performance, while competence has a positive and significant effect on employee performance. In addition, there is no indirect influence of person organization fit and competence on employee performance through work life. This study emphasizes the importance of person organization fit and competence in improving work-life balance and employee performance, although the role of intervening work-life balance in these relationships is not proven.